2015
DOI: 10.1515/jppr-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of the Iris severe mosaic virus-Ir isolate from Iran

Abstract: Iris belongs to the Iridaceae family. It is one of the most important pharmaceutical and ornamental plants in the world. To assess the potyvirus incidence in natural resources of iris plants in Iran, Antigen Coated-Plate ELISA (ACP-ELISA) was performed on 490 symptomatic rhizomatous iris leaf samples, which detected the potyvirus in 36.7% of the samples. Genomic 3' end of one mechanically non-transmitted potyvirus isolate, comprising a 3' untranslated region (390 bp) and C-terminus of the coat protein (CP) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In this context, use of reverse transcriptase PCR (RT-PCR), which works on the principle of cDNA synthesis from RNA, is one of the most promising approaches in plant viral diagnosis [ 39 ]. Using RT-PCR, Nateqi and coworkers [ 77 ] identified Iris severe mosaic virus (ISMV) using specific primers. A one-step RT-PCR is more sensitive, reliable, and cost-effective and has been employed on a wide variety of the RNA genome-based viruses in plants.…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…In this context, use of reverse transcriptase PCR (RT-PCR), which works on the principle of cDNA synthesis from RNA, is one of the most promising approaches in plant viral diagnosis [ 39 ]. Using RT-PCR, Nateqi and coworkers [ 77 ] identified Iris severe mosaic virus (ISMV) using specific primers. A one-step RT-PCR is more sensitive, reliable, and cost-effective and has been employed on a wide variety of the RNA genome-based viruses in plants.…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…Transcripts from the soybean mosaic virus was found abundantly expressed in all five tissues analyzed. Although, these viruses have been isolated from these plants (and the related species Iris) previously [18][19][20][21][22], recent studies have shown the threat posed by these viruses to saffron cultivation is seriously underestimated. Several bacterial and fungal genera incorporating known pathogen species have also been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, saffron has been shown to be infected with bean yellow MV [18] and Narcissus MV [19]. Iris, which belong to the same Iridaceae family as saffron, was shown to be infected with Iris severe MV [20,21] and Narcissus MV [22]. A recent study highlights that the threat from these MVs is seriously underestimated [23].…”
Section: Viral Transcriptsmentioning
confidence: 99%